CSR MANAGEMENT BASED TRIPLE HELIX MODEL IN NORTH SUMATRA PROVINCE - Azizul Kholis; Nasirwan Nasirwan; Sulaiman Lubis; Anggriyani Anggriyani (CERED Indonesia Institute, 2021)
This study aims to examine CSR management based on the triple helix model in compa-nies in North Sumatra Province. The research was conducted from May to July 2021 by distributing questionnaires to 112 companies operating in North Sumatra Province, 20 uni-versities and 33 district/city governments. The test is based on the triple helix model, namely the involvement of universities, companies and local governments in managing CSR so that it is more well implemented and integrated. The sampling technique for com-panies is random sampling spread over 5 major cities, namely, Medan, Pematang Siantar, Tebing Tinggi, Padangsidimpuan, and Sibolga. The results of hypothesis testing indicate that there is no difference in the perceptions of the three parties for the integration of CSR management. The test results also prove that the commitment of the three elements of the triple helix supports each other for integrated CSR management in North Sumatra Prov-ince. The limitation of this research is that there are different sampling techniques for each element of the triple helix so that sample bias is predicted. The recommendation of this re-search for further studies is to add mass media as an element to support integrated CSR management.